2010
DOI: 10.1128/aem.02289-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extracellular Polymeric Substances from Acidophilic Microbial Biofilms

Abstract: We examined the chemical composition of extracellular polymeric substances (EPS) extracted from two natural microbial pellicle biofilms growing on acid mine drainage (AMD) solutions. The EPS obtained from a mid-developmental-stage biofilm (DS1) and a mature biofilm (DS2) were qualitatively and quantitatively compared. More than twice as much EPS was derived from DS2 as from DS1 (approximately 340 and 150 mg of EPS per g [dry weight] for DS2 and DS1, respectively). Composition analyses indicated the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(169 citation statements)
references
References 45 publications
12
154
2
1
Order By: Relevance
“…Generally, the production of EPS is significantly increased under so-called adverse conditions. For example, Jiao et al (2010) found that substantially higher carbohydrate-to-protein ratios were observed for the acidophilic microbial biofilms than the previously reported ratios. And more than twice as much EPS was derived from a mature biofilm as from a mid-developmental-stage biofilm (approximately 340 and 150 mg of EPS per g [dry weight] for a mature biofilm and a mid-developmental-stage biofilm, respectively).…”
Section: Definition Characteristics and Spatial Distribution Of Epscontrasting
confidence: 43%
See 3 more Smart Citations
“…Generally, the production of EPS is significantly increased under so-called adverse conditions. For example, Jiao et al (2010) found that substantially higher carbohydrate-to-protein ratios were observed for the acidophilic microbial biofilms than the previously reported ratios. And more than twice as much EPS was derived from a mature biofilm as from a mid-developmental-stage biofilm (approximately 340 and 150 mg of EPS per g [dry weight] for a mature biofilm and a mid-developmental-stage biofilm, respectively).…”
Section: Definition Characteristics and Spatial Distribution Of Epscontrasting
confidence: 43%
“…Reichhardt and Cegelski (2013) implemented solid-state NMR to deliver quantitative insights into the composition and structure of biofilm systems. Jiao et al (2010) applied solid-state NMR and linkage analysis to characterize the polysaccharide composition and yielded limited but promising information, such as, they found that solid-state NMR cannot distinguish between the β-O-4 and β-O-3 linkages of glycosidic carbon atoms. Thus, a more in-depth analysis of purified EPS fractions is needed to illuminate the structures molecular distribution of polymers (Reichhardt et al 2015).…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, GT2 involved in biosynthesis of carbohydrates was upregulated at 46 1C, whereas GH57 involved in hydrolysis of carbohydrates was upregulated at 40 1C. The extracellular polymeric substance in AMD biofilms from the Richmond mine has been shown to contain abundant carbohydrates, including galactose, glucose, heptose, rhamnose and mannose (Jiao et al, 2010). Thus, Leptospirillum group III might act both as a source and sink to the carbohydrate pool in the biofilm matrix.…”
Section: Effect Of Warming On Leptospirillum Functionmentioning
confidence: 99%